2020
DOI: 10.1039/d0ta02517h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen vacancy and spinel phase integration on both anionic and cationic redox in Li-rich cathode materials

Abstract: The effect of oxygen vacancy and spinel phase integration on anionic and cationic redox in Li-rich cathode materials was unraveled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 71 publications
2
84
0
Order By: Relevance
“…The underlying fine structure could be revealed by the vibration near the elastic peak at 0.1–0.9 eV (Fig. 4f ) 26 , 38 . It is reported that the vibration frequency is closely related to the species of O–O dimer 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The underlying fine structure could be revealed by the vibration near the elastic peak at 0.1–0.9 eV (Fig. 4f ) 26 , 38 . It is reported that the vibration frequency is closely related to the species of O–O dimer 26 .…”
Section: Resultsmentioning
confidence: 99%
“…LMNCA‐urea‐mic and LMNCA‐EG‐mic samples have slightly increased lattice parameters compared to LMNCA‐urea‐a and LMNCA‐EG‐a. The increase in lattice parameters is due to the reduction expansion mainly caused by the reduction of transition metal cation oxidation states and the corresponding increased cation radii of the reduced transition metals cations [37, 38]. The slight increase in the lattice parameters and unit cell volume for microwave irradiation LMNCA urea‐mic and LMNCA EG‐mic suggests better lithium diffusion in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…The slight increase in the lattice parameters and unit cell volume for microwave irradiation LMNCA urea-mic and LMNCA EG-mic suggests better lithium diffusion in the structure. The small lattice contraction that maybe caused by oxygen vacancies has minor effect in the lattice parameters for nonstoichiometric compounds [37,39,40]. The I (003) /I (104) intensity ratio is usually used to characterized the degree of cation mixing in the Li layer formed by some Ni 2 + ions occupying Li + sites due to similar radii of Li + (0.76 Å) and Ni 2 + (0.69 Å) [41][42][43].…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…Ni +2/+4 , Co +3/+4 , and Mn +3/+4 contribute a maximum of 170-180 mAh g -1 capacity, whereas the bulk oxygen redox accounts for the rest of the capacity. Several theories on oxygen redox are reported in the literature [80,81]. Whatever way it takes part in the charge-discharge mechanism, it also brings in several adverse side effects when oxygen gas is released from the surface.…”
Section: Lithiation-delithiation Mechanismmentioning
confidence: 99%